Examining the Impact of Website Quality Attributes on Electronic Customer Satisfaction in Online Travel Platforms - Rizki Ramadhan; Munjiati Munawaroh (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
The rapid growth of e-commerce has intensified competition among online platforms, particularly in the online travel agency (OTA) industry. In this context, website quality plays a crucial role in shaping customer experiences and determining electronic customer satisfaction. This study aims to examine the influence of website quality attributes—namely website design, website information, website interaction, and website usefulness—on electronic customer satisfaction in the context of an online travel platform. A quantitative research approach was employed using a survey method to collect data from users of the Tiket.com platform in Indonesia. The study involved 150 respondents who had conducted at least two transactions on the platform. Data were analyzed using Structural Equation Modeling (SEM) with AMOS software to test the proposed relationships among variables. The results indicate that website design and website interaction have a positive and significant effect on electronic customer satisfaction, while website information and website usefulness do not show significant effects. Additionally, overall website quality significantly influences electronic customer satisfaction. These findings suggest that visual design and interactive capabilities play a more prominent role in shaping customer satisfaction in online travel services than informational or functional aspects alone. The study contributes to the literature on website quality and e-commerce by highlighting the differential effects of website attributes on customer satisfaction in digital service environments. The results also provide practical insights for online travel platform managers to prioritize improvements in website interface design and interactive features to enhance user experiences and customer satisfaction.